The Psychological Impact of Social Media Use on Adolescents in Iraq: A Cross-Sectional Study in Al-Diwaniyah City - Ridha , Adil Hammadi Abdul (American Journal of Biomedicine and Pharmacy, 2026)
Background: Social media has become an integral part of adolescent daily life globally, with growing evidence suggesting both beneficial and harmful psychological effects. In Iraq, where internet penetration has expanded markedly in recent years and adolescents represent a substantial portion of the population, the psychological implications of social media use remain poorly characterised. Objective: To assess the prevalence of depressive symptoms, anxiety, and low self-esteem among adolescents in Al-Diwaniyah city, Iraq, and to examine their associations with social media use patterns. Methods: A cross-sectional, school-based study was conducted among 408 adolescents aged 13–18 years in Al-Diwaniyah city between January and June 2024. Psychological outcomes were measured using the Arabic-validated Patient Health Questionnaire-9 (PHQ-9), the Generalised Anxiety Disorder-7 scale (GAD-7), and the Rosenberg Self-Esteem Scale (RSES). Social media use patterns were assessed via a structured self-administered questionnaire. Binary logistic regression was used to identify independent predictors. Results: The mean age was 15.6 ± 1.7 years; 50.0% were female. The mean daily social media use was 4.2 ± 2.1 hours, and 87.4% reported daily use. Clinically significant depressive symptoms were present in 38.6% of participants, anxiety in 41.2%, and low self-esteem in 29.5%. Daily social media use exceeding three hours was independently associated with higher odds of depression (aOR = 2.31; 95% CI: 1.64–3.26; p < 0.001), anxiety (aOR = 2.18; 95% CI: 1.53–3.10; p < 0.001), and low self-esteem (aOR = 1.87; 95% CI: 1.29–2.71; p = 0.001). Conclusion: Social media use is significantly and independently associated with adverse psychological outcomes among adolescents in Al-Diwaniyah, Iraq. Public health interventions targeting digital literacy, parental awareness, and adolescent mental health services are urgently warranted.